PENGEMBANGAN METODE ANALISIS PENETAPAN KADAR ASAM LINOLEAT DALAM MINYAK BIJI ANGGIIR OTIS VINIFERA L.) SECARA KROMATOGRAFI GAS - Agustina Sigi, Virginia
Grapeseed oil is one of the foods that contains unsaturated fatty acids. The main fatty acid component is linoleic acid. Linoleic acid has some benefits, such as proinflammatory agents during the inflammatory phase of the healing process and to overcome ultraviolet light-induced skin hyperpigmentation.. This study was aimed to develop and validate analytical methods for determining the content of linoleic acid in grapeseed oil. Grapeseed oil was obtained by soxhletation, and was derivatized to convert linoleic acid into more volatile derivate. Derivate was obtained by acid pretreatment with sulfuric acid-methanol and base transesterification with NaOH-methanol. Analysis was performed by gas chromatography using optimized condition. The optimized condition was resulted at a isothermal column temperature at 190°C for 12 minute whereas the injector and detector were kept at 250°C and 280°C. Coefficient of correlation (r) was 0.999, coefficient variance of linear regression (V,w) was 1.670%, limit of detection (LOD) was 38.480 ppm, and limit of quantization (LOQ) was 116.620 ppm. Precision test revealed a coefficent of variance of 1.910% for the first day, 0.850% for the second day, and 1.980% for the third day. Accuracy revealed a percentage of recovery in a range of 98.510-99.830 %. The developed analytical method using gas chromatography could be used to determine the concentration of linoleic acid in grapeseed oil. Concentration of linoleic acid in sample A and B were 60.233% and 70.393%, respectively.